Cost-Utility Analysis of Incobotulinumtoxin-A Compared With Conventional Therapy in the Management of Post-Stroke Spasticity in Romania - Turcu-Stiolica, Adina; Subtirelu, Mihaela-Simona; Bumbea, Ana-Maria (Frontiers in Pharmacology, 2020)
Objectives: In Romania, the strokes’ incidence is of 61,500 per year and improving upper limb function is the essence in rehabilitation after a stroke to maximise the patient quality of life and reduce disability. In this study it is compared the cost-effectiveness of the treatment of post-stroke upper limb spasticity with incobotulinumtoxin-A (INCO), with or without electromyographic control, against the conventional therapy programme alone (CON). Methods: A Markov state transition model was developed to effectuate a cost-utility analysis (CUA). Measurements of health-related quality of life were derived from relevant clinical trials. Utility values for quality of life by response status were derived from the Short-Form-12 (SF-12) Health Survey data from a published study. The incremental cost-effectiveness ratio (ICER) of INCO (fixed, every 12 weeks) against CON was calculated in Ron per quality-adjusted life-year (QALY) gained for both therapies. Costs and outcomes were discounted using different scenarios at 3% and 5% per year with a time horizon of 3 and 5 years because Romanian legislative norms don’t specify the discount rates and time horizon for pharmacoeconomic analysis. Probabilistic sensitivity analyses (PSA) were managed on the base case with distributions attributed to the frequency of repeat dosing and utility valuation of the responder and the non-responder for health utilities derived from both mental and physical health state. Results: Compared with CON, in all 4 scenarios, therapy with INCO had an incremental cost-effectiveness ratio (ICER) of less than 950 Euro per QALY gained (1 Euro = 4.7 Ron). INCO proved to be more favorable treatment option than CON in the treatment of upper limb spasticity in Romania. Despite costs being higher for patients treated with INCO, this treatment has more advantageous Incremental Cost-Effectiveness Ratio. Conclusions: This therapy should be taken into account when considering rehabilitation options because it is highly cost-effective at <EURO 1,000/QALY gained, a very low WTP (Willingness To Pay) threshold. INCO proved to be a disruptive innovation because it’s a new and more effective treatment, and, in the end, much higher in quality of life for patients with post-stroke upper limb spasticity.